CD4 cell counts in adults with newly diagnosed HIV infection in Barbados - Kilaru, Krishna R. (2004)
Seeks to evaluate the absolute CD4 cell counts of all the newly diagnosed HIV-infected persons who presented at the Ladymeade Reference Unit, which serves as the national HIV/AIDS referral and treatment centre for the country of Barbados.